D‐isosorbide and 1, 3‐propanediol as plasticizers for starch‐based films: Characterization and aging study. Issue 20 (2nd February 2017) - González, Kizkitza; Martin, Loli; González, Alba; Retegi, Aloña; Eceiza, Arantxa; Gabilondo, Nagore
ABSTRACT: In the present work, D‐isosorbide and 1, 3‐propanediol are proposed as alternative plasticizers obtained from renewable resources. Plasticized starch films were prepared by solvent casting method. The influence of using different "green" plasticizers in the final properties of starch‐based films was analyzed. Besides, the characterization of the films was also performed after storage time in order to evaluate the effect of the plasticizer on aging. UV‐spectrophotometry results showed better optical properties for both glycerol and D‐isosorbide films with higher transparency. The thermal and mechanical properties resulted influenced by the nature of the plasticizer. It was demonstrated that water vapor permeability was governed by the starch‐water interactions, whereas the oxygen permeability depended on the plasticizer's nature. The storage time affected the surface, mechanical, and thermal properties of the plasticized starch films. Atomic force microscopy results concluded that the topography of the films changed due to aging. The use of D‐isosorbide as plasticizer reduced the evolution of the mentioned properties and enhanced the reliability of the material. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44793. Abstract :